Correlation Between Platelet Index, Neutrophil-Lymphocyte Ratio, and Mean Platelet-Volume Lymphocyte Ration with Lesion in Chronic Coronary Syndrome Based on SYNTAX Score - Fathurohim, Zainal; Tjahjono, Cholid Tri; Arthamin, Maimun Zulhaidah; Kurnianingsih, Novi (Heart Science Journal, 2024)
AbstractBackground: Platelet aggregation and inflammation have been associated with atherosclerosis, and inflammatory parameters such as mean platelet volume (MPV), platelet distribution width (PDW), neutrophil-lymphocyte ratio (NLR), and mean platelet-lymphocyte volume ratio (MPLVR) are often used. However, the relationship between these inflammatory parameters and the SYNTAX Score in CAD remains uncertain.Objective : The purpose of this study was to investigate the relationship between angiographic SYNTAX score, NLR, and platelet parameters (MPV, PLR, MPLVR).Material and Methods : We conducted a study involving patients undergoing elective coronary angiography from January 2023 to June 2023 at Dr. Saiful Anwar General Hospital, who were 18 years of age or older and had CAD. All participants willingly agreed to be part of the study. We collected complete routine blood counts and performed blood biochemistry assessments 24 hours before the coronary angiography procedure. Pearson's correlation was used to examine the relationship between the variables.Result: A total of 366 individuals meeting the study's inclusion criteria were included. MPV, PLR, MPLVR, NLR, and PDW showed weak to negligible correlations with the SYNTAX Score, displaying correlation coefficients of 0.260, 0.190, 0.320, 0.470, and 0.290, respectively, all with p-values <0.001.Conclusion: This study in individuals with coronary artery disease revealed a limited to negligible correlation between the SYNTAX Score and inflammatory parameters including MPV, PLR, MPLVR, NLR, and PDW.Â